The Inshot Application Based on Local Wisdom to Improve Descriptive Poetry Writing Skills - Erdlanda, Febry Marindra Cysbya; Febrianti, Sipa Naura; Ningsih, Dinni Nurfajrin (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This article aims to describe the improvement of learning outcomes in writing descriptive poetry using the inshot application based on local wisdom in students. The research was conducted at MAN 2 Cianjur on April 14, 2025 - April 28, 2025. The population taken was all class X students at MAN 2 Cianjur, totaling 311 students with a sample class X1 for the experimental group consisted of 29 students and class X5 for the control group consisted of 29 students. All were taken by random sampling. The instrument used was a test sheet with data analysis that began with the creation of scoring guidelines, calculating DSS and DSK, and calculating the average value which was then ended with statistical analysis through SPSS for hypothesis testing and N-Gain testing to determine the increase in learning outcomes. The findings were obtained in the form of a significant increase in the average value in the post-test of the experimental class with an average value of 95 with a Classical Absorption Power (DSK) of 97% when compared to the average value in the post-test of the control class which only got an average value of 58 with a Classical Absorption Power (DSK) of 0%. In the results of the hypothesis test through the Man-Whitney data test, the Asymp.sig value was obtained. (2-tailed) 0.000 <0.05 significance level, then H0 was rejected while H1 was accepted which was supported by the results of the N-Gain test of the post-test of the experimental class with an averageN-GainThe score of 0.8963 is in the high category compared to the control class post-test which was only 0.5883 in the medium category, so it can be concluded that there is a difference in the form of increased student learning outcomes in writing descriptive poetry using the local wisdom-based inshot application.